Meningkatkan Hasil Belajar Matematika melalui Pembelajaran Tipe Cooperative Integrated Reading and Compisition (CIRC) pada Siswa Kelas VI SD Negeri 2 Sribhawono TP 2019/2020 - Damiyem, Damiyem (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The purpose of this study is to improve mathematics learning outcomes through Cooperative Learning Type Cooperative Integrated Reading and Compoisition (CIRC) in Class VI students of SD Negeri 2 Sribhawono East Lampung TP 2019/2020. This research was conducted in Class VI SD Negeri 2 Sribhawono from August to October 2019 with a total of 30 students. The research method applies Classroom Action Research. The action was carried out in three cycles and three meetings in each cycle. The results of the study indicate that the Cooperative Learning Type Cooperative Integrated Reading and Composition (CIRC) method can improve Mathematics Learning Outcomes for Class VI students of SD Negeri 2 Sribhawono East Lampung TP 2019/2020.